ANALISIS FAKTOR DETERMINAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS JATIKALEN KABUPATEN NGANJUK - Siti Nur Farida; Dwi Retno Wati (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Introduction: Anemia of pregnancy is a national problem faced by the Indonesian government because it shows the value of the socio-economic welfare of the community and affects the quality of human resources. Apart from that, anemia in pregnant women can be said to be "potential danger to mother and child". Objective: The purpose of this study was to determine the factors that influence anemia in pregnant women at the Jatikalen Public Health Center, Nganjuk Regency in 2022. Methods: This type of research is quantitative analytic with a cross sectional research design (cross-sectional). The study population was 341 pregnant women with a sample size of 79 taken by proportional random sampling. Independent variables are age, education, occupation, parity, gestational age, frequency of ANC, compliance with blood supplement consumption and knowledge, Dependent Variable of Pregnancy Anemia. Primary data based on a questionnaire and secondary data about Hb taken from the MCH handbook. Data analysis with descriptive analysis and inferential statistics Ordinal Regression. Results: Based on the results of the Ordinal Regression test analysis, data obtained from age, education, occupation, parity, gestational age, adherence to consumption of blood-added tablets and knowledge have an effect on the incidence of anemia in pregnant women. ANC frequency data does not affect the incidence of anemia in pregnant women. Conclusion: The results of the study can be concluded that simultaneously the factors that influence anemia include age, education, occupation, parity, gestational age, adherence to taking blood-added tablets, knowledge and there is no effect of ANC frequency on anemia in pregnancy. It is recommended for the Puskesmas to improve the monitoring of health workers for early detection of risk factors for anemia and for pregnant women it is recommended to consume the correct blood-added tablets.